﻿Hydrogen explosion safety for the Bilibino NPP EGP-6 reactor in conditions of a beyond design basis accident - Anatoly A. Kazantsev; Ol’ga V. Supotnitskaya; Evgeniya A. Ivanova; Irina V. Moskovchenko; Ruben I. Mukhamadeev; Vladimir F. Timofeev; Nataliya E. Astakhova (Nuclear Energy and Technology, 2023)
The paper presents the results of simulating a beyond design basis accident with regard to radiolytic hydrogen transport and analysis of hydrogen explosion safety in the reactor cavity and in the central reactor hall of the Bilibino NPP. The KUPOL-M code, version 1.10a, is used as the calculation tool for justifying hydrogen explosion safety. The accident under investigation is a beyond design basis accident, the initial event for which is spontaneous travel of two pairs of automatic control rods and a failure of the reactor scram system. The accident leads to the maximum possible release of positive reactivity, mass destruction of fuel elements, and escape of radiolytic hydrogen, as part of the gas mixture, into the reactor cavity and the central hall and further, through the broken windows, into the atmosphere. The calculation results show that no explosive concentrations of hydrogen are formed in the reactor cavity and in the central hall. Therefore, hydrogen explosion safety is ensured throughout the duration of the design basis accident for the Bilibino NPP unit with the EGP-6 reactor.